2017
DOI: 10.1021/acs.est.7b02294
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Fate of Monoethanolamine: Enhancing New Particle Formation of Sulfuric Acid as an Important Removal Process

Abstract: Monoethanolamine (MEA), a potential atmospheric pollutant from the capture unit of a leading CO capture technology, could be removed by participating HSO-based new particle formation (NPF) as simple amines. Here we evaluated the enhancing potential of MEA on HSO-based NPF by examining the formation of molecular clusters of MEA and HSO using combined quantum chemistry calculations and kinetics modeling. The results indicate that MEA at the parts per trillion (ppt) level can enhance HSO-based NPF. The enhancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
169
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(181 citation statements)
references
References 78 publications
12
169
0
Order By: Relevance
“…In addition, the cluster growth might be hindered due to kinetic barriers. The addition of a monomer or a cluster to a pre-existing cluster might require cluster reorientation which in turn may lead to the breaking of intermolecular bonds, and thus non-negligible kinetic barriers (DePalma et al, 2014;Bzdek et al, 2017;Xu et al, 2017). The subsequent growth as well as the evaporation may be slower than our calculations assume, especially in the case of strongly bound cage-like clusters.…”
Section: Ion-mediated Particle Formationmentioning
confidence: 84%
“…In addition, the cluster growth might be hindered due to kinetic barriers. The addition of a monomer or a cluster to a pre-existing cluster might require cluster reorientation which in turn may lead to the breaking of intermolecular bonds, and thus non-negligible kinetic barriers (DePalma et al, 2014;Bzdek et al, 2017;Xu et al, 2017). The subsequent growth as well as the evaporation may be slower than our calculations assume, especially in the case of strongly bound cage-like clusters.…”
Section: Ion-mediated Particle Formationmentioning
confidence: 84%
“…In addition of the commonly studied ammonia and amines, several studies have recently investigated possibilities of other bases to participate in new-particle formation. For instance, diamines, amineoxides and guanidine compounds have been suggested to have a role in the stabilization of sulfuric-acid-containing clusters (Xie et al, 2017;Jen et al, 2016;Elm et al, 2016;Myllys, 2017). In fact, these compounds are able to enhance particle formation much more effectively than ammonia or dimethylamine, however, their atmospheric abundances remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There is compelling evidence that sulfuric acid (SA), water (W), ammonia (A) or amines can play key roles in atmospheric new particle formation (NPF), but these compounds are still not e cient enough to explain NPF in all the environments where it has been observed. Recently, numerous atmospheric observations and theoretical studies have shown that organic acids can also enhance NPF, [5][6][7][8][9][10][11][12][13][14][15] However, there are potentially tens of thousands of di↵erent atmospheric organic species with varying properties, which makes the exact chemical composition of clusters containing organic molecules highly speculative. Furthermore, di↵erent organics have di↵erent chemical reactivities.…”
Section: Introductionmentioning
confidence: 99%